Dietary shifts may underpin the recovery of a large carnivore population. (27th April 2022) - Campbell, Mariana A.; Udyawer, Vinay; Jardine, Timothy D.; Fukuda, Yusuke; Kopf, R. Keller; Bunn, Stuart E.; Campbell, Hamish A.
Abstract : Supporting the recovery of large carnivores is a popular yet challenging endeavour. Estuarine crocodiles in Australia are a large carnivore conservation success story, with the population having extensively recovered from past heavy exploitation. Here, we explored if dietary changes had accompanied this large population recovery by comparing the isotopes δ 13 C and δ 15 N in bones of crocodiles sampled 40 to 55 years ago (small population) with bones from contemporary individuals (large population). We found that δ 13 C and δ 15 N values were significantly lower in contemporary crocodiles than in the historical cohort, inferring a shift in prey preference away from marine and into terrestrial food webs. We propose that an increase in intraspecific competition within the recovering crocodile population, alongside an increased abundance of feral ungulates occupying the floodplains, may have resulted in the crocodile population shifting to feed predominantly upon terrestrial food sources. The number of feral pigs consumed to sustain and grow crocodile biomass may help suppress pig population growth and increase the flow of terrestrially derived nutrients into aquatic ecosystems. The study highlights the significance of prey availability in contributing to large carnivore population recovery.